Study of foreign sociological ideas in works of G. P. Davidyuk in the 1960–80s - Dudchik, Andrei Y. (Journal of the Belarusian State University. Sociology, 2019)
The process of transfer of foreign conceptions in the works of Belarusian sociologist G. P. Davidyuk in the period of 1960–80s is analyzed. Importance of study of foreign conceptions of industrial society for his professional development and general vision of sociological knowledge is proved. Specificity of Soviet «critique of bourgeois sociology» as a form of knowledge transfer are explicated. Transformation of attitude toward foreign conceptions as a variant of «normalization» and permanent use of a number of ideas, concepts and approaches in research and education is shown.